Translects: Postqueering Transgender in Nigerian and South African Autofiction - (:unkn) unknown (My University, 2025)
Translects—our coinage (Zabus & Das, 2020)— are transnational, transgender-inflected terms rooted in ancestral contexts. Hinging on ‘transing’ and ‘translating’, I examine the use of translects in ‘autofictions’—South African Zandile Ngozi Nkabinde’s Black Bull, Ancestors and Me (2008), which I contrast with South African Anastacia Thomson’s Always Anastacia (2015), and Nigerian-born, US-based, Igbo-Tamil writer, Akwaeke Emezi’s Freshwater (2018) and Dear Senthuran: A Black Spirit Memoir (2021)—to reflect on a ‘post-queer’ and post-secular turn in approaching transgender identities and personhoods, which translate into various shades of postcolonial naming practices in Sub-Saharan Africa.
Keywords: African Research